Nature and Structure of Human Genes that Generate Retropseudogenes - Gonçalves, Isabelle (Cold Spring Harbor Laboratory Press, 2000)
The human genome is estimated to contain 23,000 to 33,000 retropseudogenes. To study the properties of genes giving rise to these retroelements, we compared the structure and expression of genes with or without known retropseudogenes. Four main features have emerged from the analysis of 181 genes associated to retropseudogenes: Reverse-transcribed genes are (1) widely expressed, (2) highly conserved, (3) short, and (4) GC-poor. The first two properties probably reflect the fact that genes giving rise to retropseudogenes have to be expressed in the germ-line. The two latter points suggest that reverse-transcription and transposition is more efficient for short GC-poor mRNAs. In addition, this analysis allowed us to reject previous hypotheses that widely expressed genes are GC rich. Rather, globally, genes with a wide tissue distribution are GC poor.